Pengaruh Pelatihan Terhadap Employee Engagement Di The ZHM Premiere Hotel Padang - Nur Hilal; Feri Ferdian (Lembaga Pengembangan Kinerja Dosen, 2024)
The motivation of this study is to find problems related to training and employee management. The research used is quantitative. The research data used primary and secondary data. The population of this study consisted of employees of ZHM Premier Padang. The research sample was 90 consumers with non-probability sampling techniques. Data was collected through likert scale questionnaires that were tested for validity and reliability. Data processed with SPSS 25.00. Training is in the category of quite agreeable at 53.33% and the Employee Engagement variable shows the agree category with a percentage of 52.22%. The training value (X) has a Beta or Standardized Coefficient of 0.507 with a calculated T (6.456) with a significance of 0.000 <0.05 with a positive and significant effect on purchasing decisions (Y). An R Square value of 0.321 was obtained, meaning that the influence of the training variable (X) had an effect on employee engagement (Y) with a positive value of 32.1% and 67.9% was influenced by other factors. So it can be concluded that there is a significant influence between the training variable (X) and employee engagement (Y).